PELANGGARAN PRINSIP KESANTUNAN BERBAHASA DALAM FILM SWEET 20 - Rahmayanti, Suci; Patriantoro, Patriantoro; Sanulita, Henny (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research was conductud because the writer found many violations of linguistic politeness principle based on the theory of politeness Geoffrey Leech in the Sweet 20 movie. This study aimed to describe violation of linguistic politeness principle in the Sweet 20 movie and to describe the implicatures that appear in the Sweet 20 movie. This research uses two qualitative method. Firstly, collecting the data based on the documentary method. Secondly, analyzing the data based on descriptive and analysis context method. The result of this research the violations of linguistic politeness principle in the Sweet 20 movie amounted to 123 speeches. The most frequent violations committed by the characters in the Sweet 20 movie were violations of the approbation maxim totaling 58 speeches, followed by maximal breaches of the agreement maxim to 31 speeches, tact maxim violations totaling 12 speeches, modesty maxim violations totaling 12 speeches, generosity maxim violations totaling 7 speeches, and sympathy maxim violations totaling 3 speeches.Â Keywords: Â Politeness Violation, Implicature, Sweet 20 Movie